2019
DOI: 10.3390/molecules24183269
|View full text |Cite
|
Sign up to set email alerts
|

Combining DNA Barcoding and HPLC Fingerprints to Trace Species of an Important Traditional Chinese Medicine Fritillariae Bulbus

Abstract: Fritillariae Bulbus is a precious Chinese herbal medicine that is grown at high elevation and used to relieve coughs, remove phlegm, and nourish the lungs. Historically, Fritillariae Bulbus has been divided into two odourless crude drugs: Fritillariae Cirrhosae Bulbus and Fritillariae Thunbergii Bulbus. However, now the Chinese Pharmacopoeia has described five Fritillariae Bulbus—the new additions include Fritillariae Pallidiflorae Bulbus, Fritillariae Ussuriensis Bulbus, and Fritillariae Hupehensis Bulbus. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…1∼18 of T. asiatica were calculated by the cosine value method of vectorial angle, and the results were detailed below: 0.9507-0.9765 of samples no. [16][17][18]. The degree of chromatographic fingerprint similarity between T. asiatica root bark and T. asiatica stem bark was much higher than that of other parts.…”
Section: Chromatographic Fingerprint Analysismentioning
confidence: 92%
See 1 more Smart Citation
“…1∼18 of T. asiatica were calculated by the cosine value method of vectorial angle, and the results were detailed below: 0.9507-0.9765 of samples no. [16][17][18]. The degree of chromatographic fingerprint similarity between T. asiatica root bark and T. asiatica stem bark was much higher than that of other parts.…”
Section: Chromatographic Fingerprint Analysismentioning
confidence: 92%
“…High performance liquid chromatography (HPLC) fingerprint technology as an important analytical method had got quick development in many areas such as TCMs, food and biological samples. It can be a relatively effective method to evaluate the quality of complex TCMs as a whole [16][17][18]. In order to further explore the differences of all medicinal parts of T. asiatica, the obtained data were statistically processed by multivariate statistical analysis including bivariate analysis, hierarchical clustering analysis (HCA) and principal component analysis (PCA).…”
Section: Introductionmentioning
confidence: 99%
“…The overall quality evaluation was established via the combination strategy between HPLC fingerprint and chemometrics [ 155 ]. What’s more, there are both HPLC fingerprints and DNA barcoding combined to analyze Fritillaria species [ 156 ]. In general, ELSD is not a commonly utilized detector, whereas the qualitative and quantitative analyses of isosteroidal alkaloids by conventional LC with DAD detector is difficult given the lack of chromophore groups.…”
Section: Analytical Techniques For Chemical Evaluation Of Fmentioning
confidence: 99%
“…Usage of the dual methods of DNA barcoding and chemical analysis (HPLC) is, thus, beneficial in screening the authenticity and quality of HMPs. Previous reports showed that a combination of DNA barcoding and HPLC successfully identified five Fritillariae bulbus species from TCM (Traditional Chinese Medicine) and its effective chemical constituents [49]. The authenticity of Eurycoma longifolia HMPs has been tested by DNA barcoding using the ITS2 marker, and its quality was verified using HPLC [50].…”
Section: Hplc Fingerprinting Of L Pumila Hmpsmentioning
confidence: 99%